A Study of Job Satisfaction among Teachers - Badril Anuar, Su @ Busu (2009)
The main purpose of this study is to examine the job satisfaction among teachers in the remote area of Sik, Kedah. Based on the objectives, several factors had been identified in influencing the job satisfaction of the teachers involved. The factors are personal factors that comprise age, gender, working experience and personality as well as organizational factors, which consist of workload, promotion and administrative supervision. These factors seem to be influencing job satisfaction. The data was collected from 73 respondents by using a structured questionnaire. The data was then analyzed using the SPSS Version 12.0 software.There were seven main hypotheses that were tested using correlation analysis. Results of the study indicate that there exists significant relationships between administrative supervision and job satisfaction (beta value = .462, p .01 – significant relationship), between workload and job satisfaction (beta value = .675, p .01 – significant relationship), between personality and job satisfaction (beta value = .574, p .01 – significant relationship) , between promotion and job satisfaction (beta value = .271, p .05 – significant relationship), and finally between gender and job satisfaction (beta value = .281, p .05). Results of the study also indicated that there exists a significant relationship with a negative value between age and job satisfaction(beta value = -.279, p .05 - significant relationship), as well as between working experience and job satisfaction (beta value = -.262, p .05 - significant relationship). Based on the results, all the factors do influence job satisfaction in both a positive and negative way. Therefore, all the factors should be taken into account and consideration when any suggestion or plan is to be made on the teachers’ job satisfaction. This is to ensure that the teachers will deliver the best services to their students, thus contributing to the development of the nation through human capital development.